Virtual Preaching : Analysis Of Happiness In Ustadz Fakhruddin Faiz's Philosophy Reciting On The Youtube Platform - Wahdah Wahdah (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2023)
The consequences of a moral crisis could be very diverse and could have a broad negative impact on individuals, society, and even the nation as a whole. It was important to take the moral crisis seriously and develop strong efforts to strengthen moral values, ethics and integrity in the lives of individuals and society. In Era 4.0 everything was digital, apart from the negative impacts there were also positive things that could be utilized, one of which was learning religion from Virtual Da'wah on various platforms, Youtube for example. This research was a qualitative research with a content analysis approach. The results of this study were that Ustadz Faiz provides virtual da'wah studies with the theme